Slope Stability Studies For Development Of Hillsite Area In Penang - Tg Razman, Tg Mohamad Shahril (Universiti Sains Malaysia, 2005)
Penang is a country that has billowy topographic hillside area and there are lots of development activities being held nowadays. Most activities are from housing and recreational development. The situation now can be dangerous to the hillside if no preventive measures be taken care; it would be disastrous for hillside development in near future. Therefore, it is important to study the slope stability for Penang hillside development. The process for this study is carried out with the help of Geography Information System (GIS) analysis software that is Erdas Imagine. With the help of this software, analysis for the critical area for hillside development in Penang can be determined. As a result, from this Geography Information System software, the result can be determined in fast and very useful to.